Du poids des mots - Stéphane Dufoix (Diasporas: Circulations, Migrations, Histoire)
Paying attention to words is nothing new in the realm of social science. However, it often remains superficial or tends to consider that words have a history that could be retraced. In this article, we will show that it is possible to understand things differently. Relying on three examples (diaspora, globalization and the French word “communautarisme”), we will propose another approach – social-historical semantics – in which the historical study of the political, social, journalistic and academic uses of words remains closely associated to the analysis of how words play a role in shaping reality. Far from being nothing but words, they can eventually acquire, through repeated used or through the importance they are granted at a certain moment in time, a very significant weight that imposes itself to almost everyone and thus transforms our comprehension of reality.